Principal's Strategies in Managing Educational Quality at Wonosari 01 State Elementary School Semarang - Angela Astrid Stelladiba Cindy Ayu; Umi Baroroh; Titik Haryati (Global Action and Education for Society, 2025)
This study explores the strategies employed by the principal of SD Negeri Wonosari 01, Semarang, in managing educational quality. As the central figure in school leadership, the principal plays a vital role in integrating various components of education curriculum, educators, infrastructure, and community involvement into a comprehensive quality management system. Using a qualitative approach through observations, interviews, and questionnaires, the research reveals that the principal adopts a transformational leadership style and applies principles of Total Quality Management (TQM). Strategic planning is conducted collaboratively, involving teachers, school committees, parents, and students. Programs such as literacy mornings, character-based learning, and extracurricular development are implemented to enhance student competencies holistically. The principal ensures continuous teacher development through supervision and professional training, while promoting a positive school culture and transparent resource management. However, several challenges persist, including limited facilities, funding constraints, and varying teacher competencies, particularly in adapting to technological tools and the new curriculum. Low parental involvement and administrative workload further hinder optimal implementation. Despite these barriers, the principal demonstrates strong commitment and adaptive leadership by fostering partnerships, encouraging innovation, and promoting continuous improvement. This research provides practical insights for school leaders aiming to enhance educational quality in public elementary schools within similar contexts.